Release experiments as an indicator of flying activities of stingless bees in urban areas - Arena, Mariana V. N.; Toppa, Rogério H.; Martines, Marcos; Alves-dos-Santos, Isabel (Frontiers in Sustainable Cities, 2023)
Contemporary urban ecology views cities as heterogeneous and dynamic ecosystems, composed of biotic, physical, social, and man-made systems. In this context, urban beekeeping stands out as a growing practice that demands further study. Many species of stingless bees (tribe Meliponini) have adapted to urban areas, while others are more sensitive. The composition of the surroundings where the beehive is located is important for the health of the nests and quality of the bee products. This work used bee capture and release techniques to evaluate the use of this methodology for releasing and monitoring native bees in urban areas and to identify whether proportion of green and gray urban nature areas affect the flying activities of stingless bees in an urban landscape. We used nests of Melipona quadrifasciata (mandaçaia), a species of stingless bees native to the Atlantic Rainforest, from three meliponaries located in different parts of the city of São Paulo. The travel time of bees in the landscape were related to the green urban areas up to 900 m in diameter from the meliponaries. Although we did not find a relationship between green areas and bee return times and numbers, it was noticeable that there was variation between the study areas, indicating that the release and monitoring methodology can be used in urban areas following the recommended modifications.